The complementarity and connectivity of locations: Digitalization, sustainability, and disruptions - Pengfei Li; Ram Mudambi (ZFW - Advances in Economic Geography, 2025)
This paper explores the intersection of international business and economic geography through the lens of connectivity and complementarity of locations. Both facets are leveraged by economic agents like multinational enterprises (MNEs). Complementarity highlights the value created by integrating diverse locational assets, addressing why locations are connected, while connectivity focuses on how linkages are established and maintained. Our framework highlights the reciprocity between the dimensions of complementarity and connectivity to foster intellectual dialogue between the two fields of international business and economic geography. Disrupted global value chains and the digital transformation of economic activities are substantially reshaping the complementarity and connectivity of locations. In this context, we emphasize the need to incorporate technological, socio-political, environmental, and geopolitical dimensions into the analysis of MNE-location interaction.
Keywords: 330; complementarity; connectivity; digitalization; location; multinational enterprises